Entrepreneurial networking and performance of small and medium paper and wood manufacturing firms in Kenya - Ongachi, Ruth Niva; Ngatia, Peter Maku; Makokha, Elizabeth Nambuswa; Miroga, Julius (American Journal of Social Sciences and Humanities, 2025)
The purpose of this study is to investigate the influence of entrepreneurial networking on performance of small and medium paper and wood manufacturing firms in Kenya. The study population were 437 small and medium paper and wood manufacturing firms in Kenya. Structured questionnaires were employed for data collection using two ways: drop and pick method and emailing survey. Pearson R correlation and multiple regression models were used to quantify the association entrepreneurial networking and performance of small and medium paper and wood manufacturing firms. Study findings established that entrepreneurial networking aspects that include entrepreneurial opportunity, diffusion knowledge and entrepreneurial culture have positive and significant influence on performance of small and medium paper and wood manufacturing firms. The study concluded that entrepreneurial networking has a positive and significant influence on performance of small and medium paper and wood manufacturing firms. The study recommends the need for small and medium paper and wood manufacturing firms to collaborate with peers in the market, participate in project workshops and events with aim of improving entrepreneurial networking. Additionally, there is need for sensitization from the ministry of trade and industry using various platforms which include shows, exhibitions, trade fairs, digital and mobile applications.